Inferring LGM sedimentary and climatic changes in the southern Eastern Alps foreland through the analysis of a 14C ages database (Brenta megafan, Italy). (15th September 2016) - Rossato, Sandro; Mozzi, Paolo
Abstract: The analysis of a database of radiocarbon ages is proposed as a tool for investigating major glaciofluvial systems of the Last Glacial Maximum (LGM) in the Alpine foreland, and their relations with glacier dynamics and climatic fluctuations. Our research concerns the Brenta megafan (NE Italy), where 110 radiocarbon dates integrate a robust regional stratigraphic and palaeoclimatic framework. Age-depth models allowed us to calculate sedimentation rates, while the time distribution of peat layers, which recurrently formed in this region during the LGM, were estimated through meta-analysis. The reliability of statistical results was carefully evaluated using Pearson and Spearman coefficients. Sedimentation rates in the Brenta megafan markedly fluctuated during LGM: ≈1.8 m/ka between 40 and 26.7 ka cal BP; ≈3 m/ka between 26.7 and 23.8 ka cal BP and ≈1.4 m/ka from 23.8 to 17.5 ka cal BP, when the distributary system deactivated due to fan-head trenching. This is evidence that sediment input and routing in the glaciofluvial distributary system was particularly efficient during the central part of LGM, when glaciers were stable at their outermost position. Meta-analysis indicates an increase in peat formation in correspondence with global (Heinrich Event 3 and/or the Greenland Interstadial 5.1 and 4 for the 30.5, 29.6 and 28.8 ka cal BP peaks) and regional (23.5 ka cal BP) wet events. Other peaks at 22.2, 21.8, 20.2 and 19 ka cal BP correlate with fluctuations of south-eastern Alpine glaciers. Significant peat formation continued until ≈18 ka cal BP, when the last peak occurred. A marked decrease in peat formation is recorded concomitantly with the onset of Heinrich Event 2 (i.e. the 26 ka cal BP trough). The good correspondence of sedimentary events in the Brenta glaciofluvial system with the dynamics of glaciers and glaciofluvial and lacustrine systems in the southern Eastern Alps suggests a common climatic forcing on the whole region during the LGM. Peat layer formation in the floodplain fens increased significantly in correspondence with glacier withdrawals and/or wetter climatic episodes, constituting a good proxy for climatic fluctuations during glacial periods. It also allows correlations across different continental environments and regions in the northern hemisphere. Highlights: 14 C ages database analysis examining LGM glaciofluvial system evolutions. The Brenta megafan aggraded with three different trends during LGM. Local climatic forcing controlled glaciers fluctuations in southern Eastern Alps. Peat production increases during climate wet events. Peat layer production correlates with climatic proxies across the N hemisphere.